Epidemiology of canine visceral leishmaniasis in a vulnerable region in Brazil - Silva, Douglas Aparecido da; Bonatto, Natália Camila Minucci; Venturin, Gabriela Lovizutto [UNESP]; Melo, Larissa Martins [UNESP]; Oliveira, Paula Lima de [UNESP]; Costa, Letícia Ramos; Bosculo, Maria Rachel Melo; Barros, Luiz Daniel de; Lima, Valéria Marçal Felix de [UNESP]; Almeida, Breno Fernando Martins de [UNESP] (FapUNIFESP (SciELO), 2021)
Visceral leishmaniasis (VL) is a neglected and endemic zoonosis that occurs throughout Brazil; nevertheless, few studies have focused on the early detection of the disease. The municipality of Ourinhos is a non-receptive, silent and vulnerable area for VL, where the seroprevalence of this disease has so far not been investigated. The present study aimed to determine the seroprevalence of canine VL in Ourinhos-SP, and to identify the presence of risk factors. Blood samples were obtained from 604 dogs during a rabies vaccination campaign together with application of a socioeconomic questionnaire, environmental and animal characteristics and tutor's knowledge about the disease. The samples were subjected to indirect ELISA and new samples were collected from reactive and suspect animals, including whole blood and lymph node aspiration evaluated by parasitological method, complete blood count and PCR. No animal was diagnosed as positive based on the combination of direct and indirect tests and the tutors' answers indicated little knowledge about leishmaniasis, being often confused with other diseases transmitted by arthropods; hence, according to the proposed methods, the presence of canine leishmaniasis in the city of Ourinhos was not confirmed and health education campaigns about the disease should be carried out.